Matrimonial Dispute Settlement: An Analysis On The Practice Of Sulh In Malaysia And Nigeria - Olufadi, Lanre Abdul Malik
The prevalence of Matrimonial Dispute within the Muslim society must not be overlooked. Many records of statistics and cases confirmed the existence of matrimonial dispute cases. However, recent studies have not painstakingly examined matrimonial disputes cases in Muslim populated countries, such as Malaysia and Nigeria. This research primarily examines the law, principles and rules relating to matrimonial dispute settlement practices under the Shari'ah courts in Malaysia and Nigeria, in the light of Sulh. The legality, conditions and principles of Sulh in Islam are explicated in this research. A brief history of countries, the law and practice of Sulh in the Shari'ah court of Malaysia and Nigeria are critically discussed. This research was conducted using a qualitative method. Similarly, available materials from both countries were judiciously utilized. The findings indicated that financial problem, mother in law' and differences between husband and wife's career are the major causes of matrimonial dispute in both countries facing matrimonial dispute. Quality of a Judge (Qadu)and roles of Sulh officers are meticulously elaborated in this research. It further shows that the matrimonial dispute settlement or reconciliation using the concept of "Sulh" as an alternative dispute resolution practice under Shari'ah rules in Malaysia and Nigeria are explicitly expounded. It is thereby recommended that effective mechanisms of matrimonial dispute settlement using Sulh should be generously provided in order to reduce the cases of divorce in Nigeria and Malaysia.